2021
DOI: 10.3390/ijms22115428
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Remodels Extracellular Matrix of Osteocommitted Mesenchymal Stromal Cells

Abstract: The extracellular matrix (ECM) is the principal structure of bone tissue. Long-term spaceflights lead to osteopenia, which may be a result of the changes in composition as well as remodeling of the ECM by osteogenic cells. To elucidate the cellular effects of microgravity, human mesenchymal stromal cells (MSCs) and their osteocommitted progeny were exposed to simulated microgravity (SMG) for 10 days using random positioning machine (RPM). After RPM exposure, an imbalance of MSC collagen/non-collagen ratio at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…According to a semiquantitative colorimetric assay, the amounts of both collagenous and non-collagenous proteins were decreased following sμg ( p ≤ 0.05) ( Figure 3 A). Earlier studies have shown similar changes in collagenous and non-collagenous protein levels after 10 days of 3D clinorotation of MSCs from human adipose tissue [ 34 ]. In addition, a decrease in alkaline phosphatase activity and ECM in rat bone marrow MSCs and human MSCs was observed after 14 days of 3D clinorotation [ 19 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 78%
“…According to a semiquantitative colorimetric assay, the amounts of both collagenous and non-collagenous proteins were decreased following sμg ( p ≤ 0.05) ( Figure 3 A). Earlier studies have shown similar changes in collagenous and non-collagenous protein levels after 10 days of 3D clinorotation of MSCs from human adipose tissue [ 34 ]. In addition, a decrease in alkaline phosphatase activity and ECM in rat bone marrow MSCs and human MSCs was observed after 14 days of 3D clinorotation [ 19 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 78%
“…Our study found that HWJMSC-EVs increased the expression of ITGB1 in chondrocytes and hBMSCs. The key role of ITGB1 in cell migration, proliferation [41], and adhesion [42] has been reported, and the TGF-β/Smad2/3 pathway is known for its ability to inhibit cell apoptosis, promote tissue regeneration [43], and promote the proliferation and differentiation of MSCs and chondrocytes [44,45]. In addition, the TGF-β/Smad2/3 pathway plays an important role in cartilage degeneration [46], maintenance of cartilage and the ECM [29,47], and inhibition of the progression of osteoarthritis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Under long-term µ g exposure, cancer cells depend on adhesion to evade cell death. Other cell types such as FTC-133 thyroid cancer cells and mesenchymal stromal cells showed a reduced ITGB1 gene expression when they were exposed to space or s-µ g conditions [ 64 , 69 ], whereas the ITGB1 mRNA was up-regulated in chondrocytes [ 70 ]. In summary, we discovered that the reaction of ITGB1 to environmental stresses such as µ g is cell-type-dependent and time-dependent.…”
Section: Discussionmentioning
confidence: 99%